Various Types of Research for Early Childhood Education - Yusran, Ramlah; Ondeng, Syarifuddin (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2024)
This research aims to understand and analyze various types of early childhood education (ECE) research based on objectives, approaches, methods, and data sources. The main issue raised is the lack of deep understanding among students and practitioners regarding the types of research relevant to improving the quality of education. The method used is a literature study, with data collection through analyzing literature from books, scientific journals, and related articles. Data is analyzed descriptively to identify each type of research’s characteristics, advantages, and disadvantages. The findings of this study show that there are four categories based on purpose, approach, method and data source. Based on purpose, there are descriptive, explanatory, exploratory, predictive, and evaluative types of research. Based on the approach, research is divided into quantitative, qualitative, and mixed methods. Based on method, there are experimental research, action research, case studies, longitudinal research, and cross-sectional research. Finally, based on data sources, research can be conducted through field, library, or laboratory research.. The results of this study contribute as a reference for researchers in the field of Early Childhood Education  to choose the right type of research based on four research categories, namely based on objectives, approaches, methods, and data sources.